2022
DOI: 10.1093/oncolo/oyab016
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospitalizations Among Older Adults with Gastrointestinal Cancers

Abstract: Background Older adults (≥65 years) with gastrointestinal (GI) cancers who receive chemotherapy are at increased risk of hospitalization caused by treatment-related toxicity. Geriatric assessment (GA) has been previously shown to predict risk of toxicity in older adults undergoing chemotherapy. However, studies incorporating the GA specifically in older adults with GI cancers have been limited. This study sought to identify GA-based risk factors for chemotherapy toxicity–related hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is consistent with findings from a recent study of patients age 70 years and older with incurable solid tumors or lymphoma and at least one impaired geriatric assessment domain, which showed that falls were associated with toxicity-related hospitalization. 13 However, the relationship between falls and hospitalization was not significant among older adults with gastrointestinal malignancy 25 and another heterogeneous cohort of older adults treated with chemotherapy. 24 Differences between these studies suggest that for each specific cancer type and related treatment, fall history may reflect different vulnerabilities that predispose older adults to toxicity-related hospitalization.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is consistent with findings from a recent study of patients age 70 years and older with incurable solid tumors or lymphoma and at least one impaired geriatric assessment domain, which showed that falls were associated with toxicity-related hospitalization. 13 However, the relationship between falls and hospitalization was not significant among older adults with gastrointestinal malignancy 25 and another heterogeneous cohort of older adults treated with chemotherapy. 24 Differences between these studies suggest that for each specific cancer type and related treatment, fall history may reflect different vulnerabilities that predispose older adults to toxicity-related hospitalization.…”
Section: Discussionmentioning
confidence: 97%
“…1,2,[20][21][22] Prior studies have been limited to claims-based retrospective data, 1,2,21,22 heterogeneous samples of older patients with different cancer types, stage, and treatment regimens, and inconsistent findings. [23][24][25][26] Hence, whether fall history can independently identify those at risk for toxicity-related hospitalization during neoadjuvant or adjuvant breast cancer chemotherapy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent investigation found that other demographic and clinical conditions are significantly associated with increased odds of hospitalization. These factors include female gender, diagnosis of gastric/esophageal cancer, polypharmacy (≥5 daily medications), decreased hearing, and patient-reported cardiac comorbidity (history of heart disease), as well as low serum albumin (<3.5 g/dL) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%